2023
DOI: 10.1111/tan.15049
|View full text |Cite
|
Sign up to set email alerts
|

The humoral and cellular response tomRNA SARS‐CoV‐2 vaccine is influenced byHLApolymorphisms

Abstract: Host genetic variability contributes to susceptibility to SARS‐CoV‐2 infection and COVID‐19 evolution and the role of HLA system has not clearly emerged, suggesting the involvement of other factors. Studying response to vaccination with Spyke protein mRNA represents an ideal model to highlight whether the humoral or cellular responses are influenced by HLA. Four hundred and sixteen workers, vaccinated with Comirnaty beginning 2021, were selected within the Azienda Ospedaliera Universitaria “Città della Salute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 56 publications
(114 reference statements)
0
6
0
Order By: Relevance
“…While our manuscript was under review, another study was published online, which confirmed our association between the HLA-A*03:01 allele and high antibody concentrations in the Italian population, using a different approach. 43 Another interesting result that emerged from our study is the association of the HLA-A*03:01 allele with an increased risk of experiencing specific side effects such as fever, chills and myalgia after vaccination with BNT162b2. In fact, the analysis showed side effects associated with the BNT162b2 vaccine to be more frequent in young and female subjects, but also in HLA-A*03:01 carriers.…”
Section: Association With Vaccination Side Effectsmentioning
confidence: 60%
“…While our manuscript was under review, another study was published online, which confirmed our association between the HLA-A*03:01 allele and high antibody concentrations in the Italian population, using a different approach. 43 Another interesting result that emerged from our study is the association of the HLA-A*03:01 allele with an increased risk of experiencing specific side effects such as fever, chills and myalgia after vaccination with BNT162b2. In fact, the analysis showed side effects associated with the BNT162b2 vaccine to be more frequent in young and female subjects, but also in HLA-A*03:01 carriers.…”
Section: Association With Vaccination Side Effectsmentioning
confidence: 60%
“…However, in this study, none of these factors were significant. Identifying specific groups unable to acquire cellular immunity based on HLA types remains a future research challenge ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the HLA alleles that showed associations with COVID-19 progression or response to the vaccine were predicted in this analysis to bind to self-epitopes showing 90% BLAST homology with the BNT-162b2 mRNA vaccine protein. For example, the HLA-DRB1*15:01 allele, predicted to bind epitopes of MEAF and ZFHX2, was positively correlated with enhancement of both anti-spike B and T cell responses in Caucasian and Japanese BNT-162b2 mRNA vaccine recipients [ 39 , 41 , 42 ]. Conversely, the allele HLA-A*24:02, which possibly recognizes epitopes of CHL1, was negatively related to the production of anti-spike antibodies after BNT-162b2 mRNA vaccination in an Italian study [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the HLA-DRB1*15:01 allele, predicted to bind epitopes of MEAF and ZFHX2, was positively correlated with enhancement of both anti-spike B and T cell responses in Caucasian and Japanese BNT-162b2 mRNA vaccine recipients [ 39 , 41 , 42 ]. Conversely, the allele HLA-A*24:02, which possibly recognizes epitopes of CHL1, was negatively related to the production of anti-spike antibodies after BNT-162b2 mRNA vaccination in an Italian study [ 41 ]. However, it is unclear whether T-cell responses are equally impaired in carriers of this HLA allele.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation